Job quality and well-being in OECD countries - Picatoste, Xose; Aceleanu, Mirela Ionela; Șerban, Andreea Claudia (Technological and Economic Development of Economy, 2021)
The lifestyle of world citizens has suffered an unprecedented impact as a result of the health crisis caused by the COVID-19. Economies and worldwide societies expect huge damages comparable to that caused by war. To the effects of this crisis on employment and wages must be added those produced in the workplace, with a foreseeable increase in job strain, not only as of the result of the health security reasons in the workplace but also to the effects on work-life balance, training and promotion possibilities, etc. This research analyses the impact of the economic situation on health, the influence of health on labour strain and on job quality. Using OECD data and a structural equation model, we have investigated the relationship between economy, health, quality of the job, work-life balance and well-being. The importance of security and safeness in the workplace is one of the items for evaluating job strain, particularly when they become even more crucial in pandemic times. This issue implicates not only the real risk of individual and social health but also a stressful situation for workers. The main contribution of our paper relies on establishing and prove causal relations among social and economic variables related to health, well-being and job quality, including safeness at the workplace. Considering that this relationship will probably become reinforced after a pandemic, like COVID-19, the actual relevance of the analysed topic and the achieved results becomes crucial.